Marketing And Business Development Strategies To Improve The Quality Of Digital Marketing And Digital Innovation In Micro, Small, And Medium Enterprises Omah Kepiting In Surabaya - Purwanti, Upik; Adiyani, Rini; Darmaningrum, Kurniawati (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2024)
A business that can build a ready innovation ecosystem will tend to have better digital marketing capabilities than other competitors. Digital marketing adoption indicates the level of use of digital marketing technology in an organization. The research aims to determine the effect of digital marketing adoption on digital marketing capabilities in Omah Kepiting Micro, Small, and Medium Enterprises in Surabaya. In this research, the data were analyzed using the PLS-SEM statistical method to determine the weight of each research indicator. The PLS-SEM method was chosen because there was an abnormality in the distribution of the data and the research required latent variable scores for further analysis. These findings are interesting because although the readiness of the innovation ecosystem does not have a direct effect on digital marketing adoption (?= 0.114; P-value > 0.05), digital marketing adoption turns out to have a significant positive impact on the company's digital marketing capabilities (?= 0.125; P- value < 0.05). Conclusion of digital transformation in improving the company's digital marketing capabilities, which can be the main driver in facing increasingly complex market dynamics and increasingly fierce competition.